A Benchmark of In-House Homologous Recombination Repair Deficiency Testing Solutions for High-Grade Serous Ovarian Cancer Diagnosis - Rodrigo Guarischi-Sousa; José Eduardo Kroll; Adriano Bonaldi; Paulo Marques Pierry; Darine Villela; Camila Alves Souza; Juliana Santos Silva; Matheus Carvalho Bürger; Felipe Azevedo Oliveira; Marcelo Gomes de Paula; Fabiana Marcelino Meliso; Luiz Gustavo de Almeida; et al. (Diagnostics, 2023)
Homologous recombination deficiency (HRD) has become an important prognostic and predictive biomarker for patients with high-grade serous ovarian cancer who may benefit from poly-ADP ribose polymerase inhibitors (PARPi) and platinum-based therapies. HRD testing provides relevant information to personalize patients’ treatment options and has been progressively incorporated into diagnostic laboratories. Here, we assessed the performance of an in-house HRD testing system deployable in a diagnostic clinical setting, comparing results from two commercially available next-generation sequencing (NGS)-based tumor tests (SOPHiA DDMTM HRD Solution and AmoyDx® (HRD Focus Panel)) with the reference assay from Myriad MyChoice® (CDx). A total of 85 ovarian cancer samples were subject to HRD testing. An overall strong correlation was observed across the three assays evaluated, regardless of the different underlying methods employed to assess genomic instability, with the highest pairwise correlation between Myriad and SOPHiA (R = 0.87, p-value = 3.39 × 10−19). The comparison of the assigned HRD status to the reference Myriad’s test revealed a positive predictive value (PPV) and negative predictive value (NPV) of 90.9% and 96.3% for SOPHiA’s test, while AmoyDx’s test achieved 75% PPV and 100% NPV. This is the largest HRD testing evaluation using different methodologies and provides a clear picture of the robustness of NGS-based tests currently offered in the market. Our data shows that the implementation of in-house HRD testing in diagnostic laboratories is technically feasible and can be reliably performed with commercial assays. Also, the turnaround time is compatible with clinical needs, making it an ideal alternative to offer to a broader number of patients while maintaining high-quality standards at more accessible price tiers.